Environmental Decision-Making in the Arctic Council: What is the Role of Indigenous Peoples? - Coote, Michaela Louise, 1989- (2015)
The Arctic Council (AC), since it arose out of the Arctic Environmental Protection Strategy (AEPS) in 1996, can still be seen as mainly concerned with environmental matters. The Council is increasingly in the spotlight as the Arctic undergoes large-scale environmental changes through increased human activity in the area and the wider impacts of climate change. The Council not only provides a discussion platform for the Arctic states, but has also been widely commended on its thorough inclusion of Indigenous Peoples (IPs), through the Permanent Participants (PPs), as the institution works to produce knowledge to inform environmental decision-making in the region. The Permanent Participants have been involved with the Council since its conception, holding full consultation rights in decisions and prior discussions. Arctic state officials, experts and indigenous representatives discuss and collaborate to research key issues, which may proceed to inform the national policy of the Arctic states. The exact role and impact of the PPs in this process is however not easy to observe, partly because the Council is a typical inter-governmental organisation where discussions often take place behind closed doors, and personal relationships can be crucial. To ascertain the role of IPs in the ACs decision-making process, interviews were carried out with those holding specialist knowledge in the Arctic Council - including Permanent Participant leaders and Working Group chairs - to ascertain by what means, and to what extent, the indigenous peoples influence decisions of the Arctic Council and potential subsequent policy developments in the nation-states. Findings show that the PPs' influence in environmental decision-making in the Council falls short of full participation, despite the ambitions of the Council to provide just this. The PPs' primary motivation is to protect the ability of IPs to live in a subsistence fashion. However, they can influence discussions on this matter only in part, as they must maneuver within the ...